Local Congestion Avoidance in Network-on-Chip - Minghua Tang; Xiaola Lin; Palesi, Maurizio (IEEE transactions on parallel and distributed systems, 2016)
Network-on-Chip (NoC) has been made the communication infrastructure for many-core architecture. NoC are subject to congestion, which is claimed to be avoided by many researchers. However, there is no completely understanding of congestion in literature, which hinders its solution. Toward this direction, we firstly carry out study on congestion in this paper. We find that congestion usually occurs at a portion of nodes in a local network region. Moreover, local congestion will significantly decrease system performance and mostly impact some particular communication pairs. Then we attempt to solve local congestion by addressing different local region size, based on Divide-Conquer approach and routing pressure. It avoids congestion in every local region by keeping routing pressure of every local region minimum. Using different local region size will create different routings. Our study shows that the local region size is closely related with the routing performance. When local region size is 5 × 5 the optimal routing performance of large size network could be achieved.